2019
DOI: 10.1088/1757-899x/673/1/012120
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanical properties on composite materials by several of severe plastic deformation (SPD) methods

Abstract: The technology of severe plastic deformation (SPD) is the process on forming metals of large plastic strain that is used for mass production in order to make ultrafine-grained (UFG). Through research on the characterization of aluminium-based composite materials with several SPD methods, the ideal variable will be obtained in producing high-strength materials. The development of a new SPD method driven by requirements simplifies the process, so that it can be applied for mass production, some of the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The mechanical properties tested were hardness using the Brinnel indentation method. Measurement of brinnel hardness reveals mechanical properties in resisting indentation loads, so that resistance to loading can be measured which states its strength [12]. Hardness is the ability of a metal to withstand plastic deformation loads [13].…”
Section: Characterization Of Al2o3 or B4c-reinforced Aluminum-based C...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties tested were hardness using the Brinnel indentation method. Measurement of brinnel hardness reveals mechanical properties in resisting indentation loads, so that resistance to loading can be measured which states its strength [12]. Hardness is the ability of a metal to withstand plastic deformation loads [13].…”
Section: Characterization Of Al2o3 or B4c-reinforced Aluminum-based C...mentioning
confidence: 99%
“…The development of ARB-based composite materials is an effective alternative method for manufacturing materials with improved mechanical characteristics. This process was developed based on the accumulative roll bonding (ARB) principle but can be easily installed in laboratory and industrial environments [12][13]. Roll compression in ARB affects the microstructure and mechanical properties of the composite material, where rolling compression can produce a uniform application of simple forces on the compressed workpiece.…”
Section: Characterization Of Al2o3 or B4c-reinforced Aluminum-based C...mentioning
confidence: 99%
“…The aim of all of them is the intense refining of the metal grain size in order to obtain superior mechanical properties. The usefulness of SPD methods in the processing of metal matrix composites has also been examined, and it was found that they can ensure an effective augmentation in the mechanical properties of the composites [37][38][39][40][41]. These advantageous properties are mainly due to metal grain refinement, while the other components present largely play the role of functional additions changing the tribological, electrical, or thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…While aluminium is the only metal that is suitable for use as a matrix material in ceramic-reinforced composites. The use of alumina as a reinforcement is able to improve mechanical properties, which only reached 48 VH and the tensile strength of 140 MPa was obtained [12][13][14][15][16][17]. While the development of composites reinforced with SiC hardness increased but also not too significant, namely hardness of 88 VH and tensile strength of 160 MPa [2].…”
Section: Introductionmentioning
confidence: 99%